Rehabilitation of patients with post-traumatic stress disorder by complementary methods - Chukhraev, Nikolay; Zukow, Walery; Vladymyrova, Nataliya; Fedorov, Serhii; Chukhraeva, Elena; Unichenko, Antonina; Chernyak, Viktor (Journal of Education, Health and Sport, 2023)
Introduction. The article analyzes the relationship between stress, post-traumatic stress syndrome (PTSD) and changes in the functioning of the neuroendocrine system. Aim. Development of a hypothesis and practical evaluation of its effectiveness based on the proposed rehabilitation protocols for patients with post-traumatic stress disorder resulting from psychoemotional stress, based on a multi-level multifactorial approach with the use of transcranial stimulation by pulse currents at the frequency of rhythms of the cerebral cortex, stimulation by light pulses at the frequencies of alpha, beta and theta rhythms of the cerebral cortex in combination with neuroacoustic correction of the neuroendocrine system. Materials and methods. The study involved 36 men, combatants, aged 28-54 full years, who gave their written consent to participate in the study. In the course of the research at the first stage, a hypothesis was formed about possible options for multifactorial multilevel effects on the central nervous system in order to rehabilitate patients with PTSD. Results. The implementation of the proposed solution is to increase the efficiency and reduce the time of rehabilitation of PTSD due to a multi-level multifactorial approach: Conclusion. The results of the study revealed positive dynamics of clinical manifestations in both groups of patients. After analyzing the data obtained (assessment of the quality of life according to the SF-36 questionnaire), it was found that the protocol of rehabilitation of patients with post-traumatic stress disorder is based on the use of a multi-level approach that allows correction.